Annotated bird sighting list for Fall 1985 compiled by James Hansen - Hansen, James L.et al (1985)
An annotated list of birds sighted by James Hansen and others. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Fall 1985. Epson - sheet feed/flatbed